History of Pharmacy Education in Nepal - Khanal, D.P.; Karki, S. (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Tribhuvan University, institute of Medicine started a two and half years’ proficiency certificate level (PCL) course in the year of 1972. This was the initiation of pharmacy education in Nepal where student could enroll after completing the school level education. Four federal Government Universities, two state Government Universities and two health science academics are conducting Bachelor of Pharmacy (B. Pharm) program in 27 pharmacy colleges with the enrollment of 815 students in academic year 2023/24. More than 55 institutions are conducting the 3 years Diploma of Pharmacy course under the affiliation of Council of Technical and Vocational Education (CTEVT) enrolling 2200 students yearly. Objective: The objective of this paper is to document the history of pharmacy education in Nepal. Method: We searched using the following terms: Pharmacy education in Nepal or Pharmacy education. Journal Article English (language) in NepJOL (Nepal Journal Online), PubMed. We also searched Google Scholar, HINARI. Reports were obtained from the references of the articles used for analysis. Inclusion criteria for published studies were those subjects who were assessed for the pharmacy education. Articles were reviewed if they were original research and the review articles. The review was limited to English language articles published in scientific literature from any part of the world. We used articles published up to May 2023. Exclusion criteria were studies that reported the pharmacy education only, the articles identified were reviewed. Data obtained were described in text and table. Results: The first pharmacy course was PCL pharmacy in TU, Institute of medicine started 51 years ago. The first B Pharm course was started in 1994 in Kathmandu University. Now, there are 27 colleges conducting B Pharm course and 55 colleges are conducting Diploma Pharmacy. Conclusion: The history of pharmacy education in Nepal is just 50 years old. Yet its achievements are remarkable.